(untitled) (Journal of Organizational Psychology, 2019)
Since 2009, substantial investments have been made to incentivize the meaningful use of electronic health records (EHR) and other health information technology (HIT). Emphasis is placed on the adoption of HIT for patient engagement, a policy priority. However, different hospitals are at different stages in their adoption. Some are hesitant and slow to adopt new HIT, while others have adopted technologies with a wide range of patient engagement functionalities. This study applies open systems theory to determine which organizational and environmental factors are salient in predicting the number of adoption of HIT functionality for patient engagement